A Study to Investigate Technopreneurship Talent for Higher Education Students [Engineering, Agriculture Engineering, and Information Technology Students in Universitas Andalas Indonesia] - Kamil, Insannul; Yuliandra, Berry; ., Taufik (International Journal of Engineering and Technology, 2018)
Lack of new business and jobs has led unemployed issues. This problem can be settled by increasing the number of new technopreneurs, entrepreneurs creating new business and jobs through technological innovations. The study is to find out technopreneurship talent of the students of faculty of engineering, agriculture engineering and information technology of Universitas Andalas. Then, they are compared by four criteria or dimensions: [1] Entrepreneurial Characteristics, [2] Absorptive Capacity, [3] Knowledge and Learning Skills, [4] Business and Communication Skills. A set of indicators is developed for each criterion and assessed qualitatively using questioners as tool. The assessments are carried out in three stages: indicators, criteria, and technopreneur talent assessment. Attitudes measurement technique is used for indicators assessment while Weighted Sum Model [WSM] is used for criteria and technopreneur talent assessment. The overall technopreneur talent assessments show that engineering students are relatively better with information technology students and agriculture engineering students are adept in some aspects of technopreneurship.Â Â